The Preconceptions of Economic Science - Veblen, Thorstein (Quarterly Journal of Economics, 1899)
Journal Article The Preconceptions of Economic Science Get access Thorstein Veblen Thorstein Veblen The University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 13, Issue 2, January 1899, Pages 121–150, https://doi.org/10.2307/1882197 Published: 01 January 1899